Development of ICT-Based Interactive Media to Improve PAI Learning Outcomes for Grade 1 Elementary School Students: Pengembangan Media Interaktif Berbasis ICT Untuk Meningkatkan Hasil Belajar PAI Siswa Kelas 1 Sekolah Dasar - Zulailiana, Susetna Lily (Universitas Muhammadiyah Sidoarjo, 2023)
The existing learning media is getting more advance along with technology advancement. One of the learning media that is widely used to increase effectiveness and efficiency in the learning process is the presence of interactive learning media based on ICT (Information and Communication Technology). The objective of this study was to reveal the development of ICT-based interactive media implemented in My Little Island Primary School Malang, with specific sub-focus on: (1) specification of ICT-based interactive media, (2) level of validity and attractiveness of ICT-based interactive media, and (3) improvement of PAI learning outcomes of students after using ICT-based interactive media.This study applied both quantitative and qualitative methods, as well as research and development designs. Data was collected through observation, interviews, questionnaires, and learning achievement tests. Techniques for data analysis included descriptive analysis and t-test analysis. This study found that: 1) Product specifications in the form of ICT-based interactive media were packaged in an application with the procedures used, namely (a) data collection, (b) planning, (c) initial product development, (d) initial product trials, (e) initial product revision, (f) field trial, and (g) final product revision. (2) According to the overall validation results, the validity level of ICT-based interactive media was 87.4% which was categorized in the valid category. The level of interest in ICT-based interactive media was 89.75% which was categorized in the appealing category. 3) The t test resulted in tcount 2.95 > ttable 1.717. This showed that there were differences of student learning outcomes in Islamic education before and after the use of ICT-based interactive media. It means that ICT-based interactive media can improve the learning outcomes of first-grade elementary school students in Islamic education.